Selection of pilot and flight attendant uniform suppliers in a private airline holding company using the Analytic Hierarchy Process (AHP) method - Wahyuni, Rossi Septy; Zaen , Miftakhul; Nursubiyantoro, Eko; Raharja, Mei; Zulkarnain , Yahya (OPSI, 2025)
The selection and assessment process of suppliers carried out by Private Airline Holding Company uses subjective assessment. It is not so transparent from the department's head with five criteria of suppliers and just enough sub-criteria. This matter inflicted a few problems, such as the goods received from suppliers not being by the amount ordered, the established quality standards, delays in estimated time delivered and received, and defects often found in the goods. Analytical Hierarchy Process (AHP) is a method that helps solve complex problems by structuring a hierarchy of criteria, stakeholders, and outcomes and by considering many things to develop values or priorities. This research aims to determine the priority criteria and sub-criteria of pilot and flight attendant uniform suppliers and the priority order of the best suppliers, Private Airline Holding Company. This research uses Expert Choice V.11 software to implement the AHP method. The overall evaluation obtained shows that five criteria and thirteen sub-criteria were used. The best supplier based on data processing is Supplier 1, with a value of 0.213.